Deprenyl in Tourette's Syndrome and ADHD - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1996)
The efficacy of deprenyl, a monoamine oxidase inhibitor, was evaluated in the treatment of ADHD in 24 children and adolescents with comorbid Tourette's syndrome (TS) enrolled at the University of Rochester and Baylor College of Medicine.